Genetic Diversity and Geographic Distribution of Cucurbit-Infecting Begomoviruses in the Philippines - Neoh, Zhuan Yi; Lai, Hsuan-Chun; Lin, Chung-Cheng; Suwor, Patcharaporn; Tsai, Wen-Shi (Plants (Basel), 2023)
Cucurbits are important economic crops worldwide. However, the cucurbit leaf curl disease (CuLCD), caused by whitefly-transmitted begomoviruses constrains their production. In Southeast Asia, three major begomoviruses, Tomato leaf curl New Delhi virus (ToLCNDV), Squash leaf curl China virus (SLCCNV) and Squash leaf curl Philippines virus (SLCuPV) are associated with CuLCD. SLCuPV and SLCCNV were identified in Luzon, the Philippines. Here, the genetic diversity and geographic distribution of CuLCD-associated begomoviruses in the Philippines were studied based on 103 begomovirus detected out of 249 cucurbit samples collected from 60 locations throughout the country in 2018 and 2019. The presence of SLCCNV and SLCuPV throughout the Philippines were confirmed by begomovirus PCR detection and viral DNA sequence analysis. SLCuPV was determined as a predominant CuLCD-associated begomovirus and grouped into two strains. Interestingly, SLCCNV was detected in pumpkin and bottle gourd without associated viral DNA-B and mixed-infected with SLCuPV. Furthermore, the pathogenicity of selected isolates of SLCCNV and SLCuPV was confirmed. The results provide virus genetic diversity associated with CuLCD for further disease management, especially in developing the disease-resistant cultivars in the Philippines as well as Southeast Asia.